On the Stark Broadening of Be II Spectral Lines - Milan S. Dimitrijević; Magdalena Christova; Sylvie Sahal-Bréchot (Data, 2020)
Calculated Stark broadening parameters of singly ionized beryllium spectral lines have been reported. Three spectral series have been studied within semiclassical perturbation theory. The plasma conditions cover temperatures from 2500 to 50,000 K and perturber densities 1011 cm−3 and 1013 cm−3. The influence of the temperature and the role of the perturbers (electrons, protons and He+ ions) on the Stark width and shift have been discussed. Results could be useful for plasma diagnostics in astrophysics, laboratory, and industrial plasmas.